Exploring variability in basal ganglia connectivity with functional MRI in healthy ageing - Griffanti, L; Stratmann, P; Rolinski, M; Filippini, N; Zsoldos, E; Mahmood, A; Zamboni, G; Douaud, G; Klein, J; Kivimäki, M; Singh-Manoux, A; Hu, M; et al. (Springer, 2018)
Changes in functional connectivity (FC) measured using resting state fMRI within the basal ganglia network (BGN) have been observed in pathologies with altered neurotransmitter systems and conditions involving motor control and dopaminergic processes. However, less is known about non-disease factors affecting FC in the BGN. The aim of this study was to examine associations of FC within the BGN with dopaminergic processes in healthy older adults. We explored the relationship between FC in the BGN and variables related to demographics, impulsive behaviour, self-paced tasks, mood, and motor correlates in 486 participants in the Whitehall-II imaging sub-study using both region-of-interest- and voxel-based approaches. Age was the only correlate of FC in the BGN that was consistently significant with both analyses. The observed adverse effect of ageing on FC may relate to alterations of the dopaminergic system, but no unique dopamine-related function seemed to have a link with FC beyond those detectable in and linearly correlated with healthy aging.